Pendidikan Kesehatan dengan Media Audio Visual dalam Meningkatkan Pengetahuan Remaja Tentang Resiko Pernikahan Dini - Ayu Wlandari; Nurul Ilmi; Antoni Eka FM; Dina Fithriana; Nurhayati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: The early age marriage in Indonesian is ranked seventh in the world. Compare to Java and Bali, the prevalence of early marriage in West Nusa Tenggara is the highest according. In West Lombok, especially in Kecamatan Lembar, the number of early marriage (between the age of 16 to 19) is increasing every year as many as 28 cases. Objective: Analyzing the influence of knowledge before and after being given health education about the risks of early marriage using audiovisual media. Method: This research was designed as a PreExperimetanl design with One group pretestposttest. The sampling technique used was Probability Sampling, namely Simple Random Sampling. The research population was 368. The sample was determined by using the Slovin formula, obtained as many as 61 respondents. Data of the research was collected by employing questionnaire and then analyzed by using the Wilcoxon signed rankings test with an error rate of 5%. Results: The research result indicates that there was an effect of providing health education with audio-visual media on increasing adolescent knowledge about the risk of early marriage at SMAN 1 Lembar with a value of p = 0.000 (p <0.05)